ASSESSMENT ON THE IMPLEMENTATION OF PLOT RATIO AS A DEVELOPMENT CONTROL TOOL IN GEORGE TOWN, PENANG - Abd Razak, Syafiqah Humairah; Yin, Izuandi (PLANNING MALAYSIA, 2021)
This paper investigates the changes of buildings to what extent the regulations related to plot ratio are implemented in the city of George Town, Penang, give impact on land use distribution. This study used a quantitative method by conducting field observations to identify building heights in the city of George Town, which was divided into two segments of the road. Then, GIS software was also used as one of the instruments to map the compliance analysis on study area in the city for the development control tool. The results show that quantitatively, the buildings along Jalan Dato Keramat that have been monopolised by residential activities acquire a higher building height and the maximum of plot ratio caps. There is only a small portion in Jalan Gurdwara that complies with the plot ratio limit. However, the characteristics of the area were determined by several parameters, such as building height, zoning land use activities, and building conformity. Thus, more detailed regulations regarding the changes in shape and plot ratio cap according to zoning activities on the exact location and activities are highly required.